Assessing consumer's willingness to pay for improved domestic water services in Kelantan, Malaysia - Kamaludin, Mahirah; Abdul Rahim, Khalid; Radam, Alias (ARF Publication Sourcing, 2013)
This study aims to estimate willingness to pay (WTP) of people in the state of Kelantan, Malaysia for improvement in their domestic water services. Their water sector has been a long debate since their poor water services have threatened people’s daily routine such as water disruption, water leakage, smelly and dirty water supply. The water services should be managed effectively based on efficient water pricing since any improvement in services involve high cost in its operation. A Contingent Valuation Method (CVM) was employed to 552 households in the state for analysis regarding to the services and Probit model was used to analyse the data obtained through the survey. The results show that bid price, household income and household size have statistically significant impact on WTP and they are as expected in earlier studies. The calculated mean WTP is RM0.60 applied on the first 35m3 and it is much higher from current water price. The new water price can be recommended for any improvement and upgraded services to high standard in services in the future which is satisfying consumer’s needs.